Factor analysis of bitterness in cucumis melo var.conomon Mak - Annie Mathew (Department of Olericulture, College of Horticulture, 2005)
The research project entitled ‘Factor analysis of bitterness in Cucumis melo var. conomon Mak. was carried out in the Department of Olericulture, College of Horticulture, Kerala Agricultural University, Vellanikkara, Thrissur, during the period 2000-2003. The objective of the study was to characterize bitterness and its’ persistence under varying genetic, physiologic and management contexts. The material selected was Mudicode, which is a well accepted non bitter variety. Homozygous bitter and non bitter lines obtained by continuous selfing for four generations was utilised for the study. The bitter and non bitter parental lines were crossed and F1, F2, BC1, and BC2 populations were generated. The 2 test for F2 and backcross generations with the ratio 13:3 (bitter:non bitter) showed the presence of inhibitory gene action for bitterness suggesting the possibility of introduction of inhibitory gene from wild bitter forms to the cultivated non bitter types. This is supported by the studies of the cross between oriental pickling melon and Cucumis melo var. callosus. The F1 of this cross produced small bitter fruits with characteristics similar to the bitter parent and the segregation pattern in F2 generation revealed the presence of inhibitory gene action in the ratio 13:3. To find the metaxenic effect of bitterness, several bitter wild and four cultivated cucurbitaceous species including the bitter type of Mudicode Local were used as pollen source on non bitter oriental pickling melon. The resultant fruits of these crosses were non bitter, thus ruling out the possibility of metaxenia. The study on effect of different sources of nutrients on bitterness revealed that the application of chemical fertilizers or organic manures viz., farmyard manure, neem cake, groundnut cake, poultry manure and goat manure will not modify bitterness in fruits of oriental pickling melon. Application of lime or furadan also did not change expression of bitterness. The change in physiological condition of the plant by pruning operations also did not alter the innate nature of bitterness. Similarly, the age of the plant did not show any relation with the existence of bitterness in oriental pickling melon. Comparison of morphological characters of bitter and non bitter plants showed that seeds from bitter fruits were smaller having more initial seedling vigour. Also, the fruits borne on bitter plants were more in number with smaller size, indicating the closeness of bitter plants to wild relatives. It was observed that the seeds are always non bitter irrespective of its origin from bitter and non bitter plants. But the cotyledon, hypocotyls and radicle of seedlings will remain bitter. Hence organoleptic evaluation of a part of the cotyledon, which will not hinder further development of the plant can be used as a method for identification of bitterness at an early stage. Results of biochemical analysis revealed that the content of cucurbitacin, phenol, aminoacid and polyphenol oxidase activity was higher in bitter fruits compared to non bitter fruits. The bitter principle was the highest at placental region followed by flesh and rind. In general, stalk end of the fruit was more bitter than blossom end of the fruit. The results also revealed that bitterness decreased with fruit maturity. This was substantiated using thin layer chromatography. Electrophoretic studies of seed protein showed no difference in banding pattern for bitter and non bitter seeds, indicating the closeness of the two types.